Anticoagulant activities of piperlonguminine in vitro and in vivo - Lee, Wonhwa (Korean Society for Biochemistry and Molecular Biology, 2013)
Piperlonguminine (PL), an important component of Piper longum fruits, is known to exhibit anti-hyperlipidemic, antiplatelet and anti-melanogenic activities. Here, the anticoagulant activities of PL were examined by monitoring activatedpartial-thromboplastin-time (aPTT), prothrombin-time (PT), and the activities of thrombin and activated factor X (FXa). The effects of PL on the expressions of plasminogen activator inhibitor type 1 (PAI-1) and tissue-type plasminogen activator (t-PA) were also tested in tumor necrosis factor-α (TNF-α) activated HUVECs. The results showed that PL prolonged aPTT and PT significantly and inhibited the activities of thrombin and FXa. PL inhibited the generation of thrombin and FXa in HUVECs. In accordance with these anticoagulant activities, PL prolonged in vivo bleeding time and inhibited TNF-α induced PAI-1 production. Furthermore, PAI-1/t-PA ratio was significantly decreased by PL. Collectively, our results suggest that PL possesses antithrombotic activities and that the current study could provide bases for the development of new anticoagulant agents. [BMB Reports 2013; 46(10): 484-489]